O financiamento hipotecário da cafeicultura no vale do Paraíba paulista (1865-87) - Marcondes, Renato Leite [UNESP] (Fundação Getúlio Vargas, 2002)
This paper analyses the importance of mortgage credit for the growth of the coffee economy in the Paraíba valley region, using as documentary sources three mortgage books from the localities of Guaratinguetá and Lorena. The paper shows how the traditional credit practices gave way to banking ones after the mortgage law of 1864/65. Nevertheless, only a small percentage of the population benefited from the new form of financing, with the wealthier ones enjoying the best credit facilities.

Este artigo analisa a importância do crédito hipotecário para o desenvolvimento da economia cafeeira no vale do Paraíba paulista, com base em três livros de hipotecas referentes às localidades de Guaratinguetá e Lorena. O artigo mostra a trasnformação das formas tradicionais de crédito (usurário) para a bancária a partir da lei hipotecária de 1864/65. Apesar das mudanças, o financiamento manteve-se restrito a uma pequena parcela da população e os mais afortunados conseguiam condições mais facilitadas.
Keywords: mercado de capitais; economia cafeeira; história econômica paulista